Teologi Konversi Agama yang Perenial: Suatu Interpretasi Multi-Iman Kisah Para Rasul 9:1-19 dari Konsep Sufi Wahdat al-Adyan (Kesatuan Agama-agama) - Abdillah, Aldi (Indonesian Journal of Theology, 2023)
The phenomenon of religious conversion can incite fear and prejudice against other religions, particularly those exhibiting radical moments and movements. Within the diverse context of Indonesia, the multifaceted yet deeply personal dimensions of such radical religious conversions invite further examination. A prominent historical figure who experienced such a radical religious conversion was Paul the Apostle. This article considers the text of Acts 9:1-19, which narrates his mystical encounter with Jesus while on the way to persecute the primitive Christian community in Damascus. It then moves to consider the mystical notion of Wahdat al-Adyan, or the Unity of Religions, as articulated centuries later by the Sufi mystic, Al-Hallaj (858-922 CE). My aim is to propose a theology of perennial religious conversion, or considering the religious conversion as a mystical, esoteric, and syncretic event. To do this, I adopt a perennialist philosophy as my primary framework for exploring the phenomenon of religious conversion. Informed by one of the religious conversion aspect of the Christian New Testament and mystical Islamic teachings, the multi-faith hermeneutic I construct provides opportunities to understand a given sacred text (Christianity) from the perspective of another religious tradition (Islam), thereby yielding a theology of religious conversion that is deeply relevant given Indonesia’s diversity.